Health and aging: development of the Irish Longitudinal Study on Ageing. - KENNY, ROSE; CRONIN, HILARY; FINUCANE, CIARAN; O'REGAN, CLAIRE (My University, 2013)
To assist researchers planning studies similar to The Irish Longitudinal Study on Ageing (TILDA), concerning the development of the health assessment component, to promote use of the archived data set, to inform researchers of the methods employed, and to complement the accompanying article on normative values. DESIGN: Prospective, longitudinal study of older adults. SETTING: Republic of Ireland. PARTICIPANTS: Eight thousand five hundred four community-dwelling adults who participated in wave 1 of the TILDA study. MEASUREMENTS: The main areas of focus for the TILDA health assessments are neurocardiovascular instability, locomotion, and vision. RESULTS: The article describes the scientific rationale for the choice of assessments and seeks to determine the potential advantages of incorporating novel biomeasures and technologies in population-based studies to advance understanding of aging-related disorders. CONCLUSION: The detailed description of the physical measures will facilitate cross-national comparative research and put into context the normative values outlined in the subsequent article.
PUBLISHED
PMID: 23662719
Keywords: The Irish Longitudinal Study on Ageing (TILDA); Ageing